Antibiotics prescription pattern in COVID-19 patients presenting in DHQ Teaching Hospital Sahiwal; Is Pakistan heading towards Post-COVID Antibiotic Resistance Era? - Muhammad Waseem , Maryam Rafiq , Adeela Munir , Zahid Kamal , Nauman Aziz ,Muhammad Junaid Iqbal (Journal of Rawalpindi Medical College, 2021)
Background There is a lack of data about antibiotic prescription trends and patterns of inappropriate antibiotic stewardship in COVID-19 patient management. Objective To determine frequency and pattern of antibiotic prescription in COVID-19 patients presenting in DHQ teaching hospital, Sahiwal. Methods This observational cross-sectional prospective study was conducted from 1st June 2020 to 31st March 2021 in patients admitted in COVID isolation facility of DHQ Teaching hospital, Sahiwal with confirmed COVID-19 infection. Patients of all ages and of both genders were included. Data was collected by a pre-designed proforma. Data included patient’s age, gender, co-morbid conditions, type and duration of antibiotic use, and details of prescribing physicians. Descriptive statistics were applied to determine frequency and percentages of variables. Results Out of 800 participants, 543(67.8%) were males, and the remaining 257 (32.1%) were females. The majority 328(41%) of patients belonged to the age group 40-60 years. 639(79.8%) patients had co-morbidities. Diabetes mellitus was the most common co-morbid condition 248 (31%). Antibiotics were prescribed to all patients 800 (100%) before admission to the COVID Isolation facility. The majority of patients 348 (43.5%) had used antibiotics for 3-7 days before admission. Macrolides class was the most commonly prescribed antibiotic 417 (52.1%). General practitioners had more tendency to prescribe antibiotics 509(64%) as compared to medical specialists 212(26.5%) and pulmonologists79 (9.8%). Conclusion Antibiotic stewardship needs to be improved in COVID-19 patients and prescription should be evidence-based aided by laboratory tests. The development of local guidelines for judicious antibiotic prescription in COVID-19 will help in preventing antibiotic resistance. Key Words Antibiotics, antibiotic resistance, COVID-19, drug prescription, SARS-cov-2